2010
DOI: 10.1179/174313209x459129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of platelet transfusion on hematoma expansion in patients receiving antiplatelet agents before intracerebral hemorrhage

Abstract: This study suggests that platelet administration does not reduce the frequency of hematoma expansion in ICH patients receiving antiplatelet medications. This lack of efficacy may relate to transfusion timing, as a significant proportion of hematoma expansion occurs within 6 hours post-ictus. Additionally, the increased rates of hematoma expansion in the clopidogrel cohort may relate to its prolonged half-life. A larger, prospective study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…We confirmed the results of previous studies [6,7] that demonstrated that platelet transfusion does not have a significant impact in preventing hematoma expansion, among patients taking aspirin. Of the patients that did not receive a transfusion, 29% of patients had an expansion, while 41% had an expansion following a transfusion.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We confirmed the results of previous studies [6,7] that demonstrated that platelet transfusion does not have a significant impact in preventing hematoma expansion, among patients taking aspirin. Of the patients that did not receive a transfusion, 29% of patients had an expansion, while 41% had an expansion following a transfusion.…”
Section: Discussionsupporting
confidence: 94%
“…The significant correlations [5,6] between aspirin use and poor outcome following ICH, probably due to hematoma expansion, suggest that minimizing hematoma growth should be a primary aim in the treatment of patients with aspirin associated ICH. Several studies reported that platelet transfusion for reversing antiplatelet therapy does not have a significant impact on the clinical outcome and does not prevent hematoma expansion [6,7]. The authors suggest that in the majority of these cases, hemorrhage expansion had already occurred before platelets were transfused.…”
Section: Introductionmentioning
confidence: 87%
“…Similarly, Creutzfeldt et al 20 in their analysis of 121 patients taking antiplatelet medications with spontaneous ICH found that platelet transfusion did not improve mortality. Another retrospective analysis of patients on antiplatelet therapy with spontaneous ICH by Ducruet et al 21 showed platelet transfusion did not reduce the rate of hemorrhage progression.…”
Section: Discussionmentioning
confidence: 98%
“…Among the agents used to reverse APA effects, PLTs act directly to reverse functional interference by APAs. There are opinions in favor of PLTs 20,22) and opposed 23,24) . If effectiveness of PLT transfusion is to be proved, appropriate timing and volume to achieve hemostasis must be addressed.…”
Section: Discussionmentioning
confidence: 99%